“Too Visible: Race, Gender and Resistance in the Construction of a Canadian Identity in the Poetry of Himani Bannerji” - Arce ´´Álvarez, María Laura (Miscelánea: A Journal of English and American Studies, 2007)
Canadian literature stands as an example of postcolonial writing. The literature of the Diaspora questions and reshapes basic concepts of multicultural societies like national identity, community and race. These establish a division between the white European identities accepted by the colonial governments and the others, those who in exile try to find a space to live in this new multicultural society. Canada, as a postcolonial society, is a space where different cultures and religions meet but which does not seem to fit in the definition of the Canadian individual imposed by white European cultural imperialism. Thus the others, that is, the exiled individuals, write literature to create a space suitable for their condition as immigrants and, in it, construct their own identities as ‘double-consciousness’ people. The intention of this paper is to analyze the poetry of the South-Asian Canadian writer and critic Himani Bannerji especially focusing on the use of metaphors related to race and gender in her attempt to use them as the elements that build the space and identity of the second type of individual referred to above. They are also weapons of resistance against the suffering, marginalization and subordination imposed by cultural imperialism.